INTERROGATING THE ADVANCE OF AGRIBUSINESS IN THE AMAZON: PRODUCTION, RENT AND POLITICS /Interrogando o Avanço do Agronegócio na Amazônia: Produção, Renda e Política - Ioris, Antonio Augusto Rossoto (REVISTA NERA, 2018)
The political-economy of the agriculture frontier in the Brazilian state of Mato Grosso, in the southern sections of the Amazon Region, is analysed in order to question the productivist argument commonly presented by the agribusiness sector. The assessment makes use of the category of rent considered as a proportion of exchange value diverted from production for the payment to the landowners and its class-based allies. The frontier in Mato Grosso has had basically three main rent extraction periods: a first moment when rent was forged by the state apparatus (1970s-1980s), a second period with serious turbulence and a macroeconomic transition (1980s-1990s) and a third phase with more complex flows of rent due to the neoliberalization of agribusiness (since the late 1990s). At the frontier of agribusiness, agricultural activity depends on combined strategies of rent creation and rent extraction. Empirical results suggest that rent is more than just the extraction of value from the use of land, but there is a wider capture of value from the network of relations that maintain land in production. Rent derives from land through the formation of a powerful network state-landowners-private agroindustrial sector that provides the conditions for rent extraction.